ANALISIS DISTRIBUSI OBAT DENGAN PENDEKATAN TRAVELLING SALESMAN PROBLEMS (TSP) DI PT. PHAROS CABANG PEKANBARU - Dedi Dermawan; Vedri Ramadiansyah (Jurnal Teknik Industri Terintegrasi, 2018)
PT. Pharos Indonesia is engaged in pharmaceuticals which at once distributes these medicines to certain retailers to be accessible to any community. One branch of PT. Pharos Indonesia, which is located the way of Harapan Raya, Pekanbaru, Riau. This company has distributed to various retailers in the Pekanbaru area. From the results of interviews that have been conducted on several employees, it can be concluded that the company has a problem that is about the distribution of goods that have been circulated to several retailers who have had a long time, so that the salesman feels the effects of fatigue caused by long distances and routes that are not arranged with well.                     Based on the results of data processing with the Traveling Salesman Problem (TSP) method, the proposed routes for distributing drugs to retailers as initial consumers of PT. Pharos Indonesia starts with distributing medicine  to Alzi Pharmacy - Supermarket AA - Supermarket 462 - Kimia Farma – Medicine Store Adinda - Klinik Aisyiyiah - RSIA Zainab - Drug Store Abel - Tiga Putri Pharmacy - Return to the office.